2007
DOI: 10.1007/s10750-007-9069-2
|View full text |Cite
|
Sign up to set email alerts
|

Small prey size offers immunity to predation: a case study on two species of Asplanchna and three brachionid prey (Rotifera)

Abstract: We tested the hypothesis that small prey can coexist with large predators. For this we confronted two predators (smaller Asplanchna brightwellii: 900 mm and larger A. sieboldi: 1400 mm) with three prey rotifers (smaller: Anuraeopsis fissa (70 mm); larger: Brachionus calyciflorus (200 mm) and intermediate: B. patulus (120 mm)) using functional response, prey preference, population growth and life table demography. Regardless of prey type, A. sieboldi was able to consume more prey than A. brightwellii and it con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
4
21
0
1
Order By: Relevance
“…We presumed, at times of higher transparency, that the increased risk of fish predation also caused copepods to shift to the littoral zone, generating significant differences in their spatial distribution which is in compliance with results of MIRACLE et al (2007). Furthermore, we explained that the peak of abundance of the predator A. priodonta in the first part of spring by a positive correlation with its prey, K. cochlearis (SARMA and NANDINI, 2007). We can conclude that microfilter-feeders show more differences along a spatial scale (mainly feed on detritus), while macrofilter-feeders follow seasonal patterns in their abundance as they are dependent on phytoplankton production.…”
Section: Discussionsupporting
confidence: 74%
“…We presumed, at times of higher transparency, that the increased risk of fish predation also caused copepods to shift to the littoral zone, generating significant differences in their spatial distribution which is in compliance with results of MIRACLE et al (2007). Furthermore, we explained that the peak of abundance of the predator A. priodonta in the first part of spring by a positive correlation with its prey, K. cochlearis (SARMA and NANDINI, 2007). We can conclude that microfilter-feeders show more differences along a spatial scale (mainly feed on detritus), while macrofilter-feeders follow seasonal patterns in their abundance as they are dependent on phytoplankton production.…”
Section: Discussionsupporting
confidence: 74%
“…These findings are consistent with previous works associated with competition between rotifers of different size under various food levels (Sarma et al, 1996(Sarma et al, , 1999. However, compared to B. calyciflorus, B. patulus is more vulnerable to predatory Asplanchna (Iyer & Rao, 1996;Nandini et al, 2003;Sarma & Nandini, 2007). Therefore, as shown in the present work, B. patulus, a superior competitor in non-predator environments, becomes an inferior competitor in the presence of a predator.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies showed that B. patulus was competitively superior to B. calyciflorus (Sarma et al, 1999), however, it was also more vulnerable to predatory Asplanchna than B. calyciflorus (Iyer & Rao, 1996;Nandini et al, 2003;Sarma & Nandini, 2007). Therefore, we hypothesized that the superior competitive status of B. patulus would be altered in the presence of predatory Asplanchna, and moreover, this alteration could be influenced by different intensities of predation imposed by different densities of Asplanchna.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…These include the presence of large and small spines in Plationus macracanthus and Brachionus budapestinensis, respectively (Garza-Mouriño et al, 2005), darting behaviour in Filinia longiseta and Hexarthra mira (Iyer & Rao, 1996), small body size in Anuraeopsis fissa (Sarma & Nandini, 2007), epizoic behaviour in Brachionus rubens (Iyer & Rao, 1995) and colonial life or production of toxins as in Sinantherina semibullata (Felix et al, 1995). Little information is available on the defense strategies of littoral rotifers.…”
Section: Introductionmentioning
confidence: 99%